A Vertically Integrated Project (VIP) as a learning experience to foster entrepreneurship education - Morini, Cristiano; Azevedo, Anibal Tavares; Inácio Júnior, Edmundo; Coyle, Edward J. (REGEPE Entrepreneurship and Small Business Journal, 2023)
Purpose: we aim is to present a learning approach for students to work on a hands-on project that may be applied to different contexts. This experience relates to an initiative to foster entrepreneurial education embedded in economic sustainability based on the best local practices (highest-ranked municipalities) that we find and analyze to solve complex problems in the business environment. Design/Methodology/Approach: our approach is to collaborate with policymakers at the municipal level via a research-based project approach called Vertically Integrated Project (VIP). In our VIP, students work with instructors in a long-term effort to identify challenges and opportunities by working with the community to analyze problems, develop solutions (with different techniques and approaches), and monitor their implementation. Findings: new learning approaches can engage the students in real-world problem, adding value to their formation and giving back to society the investment they made in the Brazilian public university. Originality: this initiative is in tune with the 4th and the 11th sustainable development goals (SDGs) adopted by the United Nations (UN). Practical implications: this study aims to stimulate entrepreneurial education using multidisciplinary and alternative learning approaches. Social implications: this approach can deliver SDG-related impact to local communities by linking research-based teaching with community outreach. JEL Code: L26, M10, H75, I23